The Influence of Entrepreneurial Motives, Family Environment and Financial Literacy on Entrepreneurial Intentions - Wicaksono, Putri Nur Hidayati; Mardi, Mardi; Respati, Dwi Kismayanti (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The high level of poverty and low entrepreneurship ratio in Indonesia have encouraged the government to increase the number of young entrepreneurs. By focusing on students of the Jakarta State University Entrepreneurial Student Program (Program Mahasiswa Wirausaha/PMW), this research aims to explore the influence of entrepreneurial motives, family environment, and financial literacy on entrepreneurial intensity. quantitative and uses survey research methods. This research uses dependent variables and independent variables. The results of quantitative research with 165 respondents show that partially entrepreneurial motives and family environment have a positive and significant influence on students' entrepreneurial intensity. Research recommends the need for entrepreneurship development programs that can strengthen entrepreneurial motives and create a family environment that supports student entrepreneurial activities. Although financial literacy has not been proven to have a significant effect, research highlights the importance of paying attention to other aspects that may be more dominant in motivating students to become young entrepreneurs. These findings provide a basis for development policies and educational programs that are more effective in increasing the intensity of entrepreneurship among students, so that they can make a positive contribution to the economy and reduce poverty levels.